Methyl-CpG binding domain 4 tagging polymorphisms and esophageal cancer risk in a Chinese population. Issue 2 (March 2015) - Yin, Jun; Shi, Yijun; Zuo, Junbo; Tang, Weifeng; Wang, Liming; Wang, Xu; Shao, Aizhong; Ding, Guowen; Liu, Chao; Liu, Ruiping; Chen, Suocheng; Gu, Haiyong; et al.
<x xml:space="preserve">Abstract</x> In 2009, esophageal cancer was recorded as the fifth most commonly diagnosed cancer and the fourth leading cause of cancer-related death in China. Esophageal squamous cell carcinoma (ESCC) accounts for more than 90% of esophageal cancers. Genetic factors might play an important role in the carcinogenesis of ESCC. We conducted a hospital-based case–control study to evaluate the association between methyl-CpG binding domain 4 (MBD4) rs3138373 A>G, rs2005618 T>C, and rs3138355 G>A tag single nucleotide polymorphisms and the risk of developing ESCC. A total of 629 ESCC patients and 686 controls were recruited. Genotypes were determined using the ligation detection reaction method. When the MBD4 rs3138355 GG homozygous genotype was used as the reference group, the GA, AA, and GA/AA genotypes were not associated with ESCC risk. In the recessive model, when the MBD4 rs3138355 GG/GA genotypes were used as the reference group, the AA homozygous genotype was associated with a 28% decreased risk for ESCC (AA vs. GG/GA: adjusted odds ratio=0.72, 95% confidence interval=0.53–0.99, P=0.040). The MBD4 rs3138373 A>G and rs2005618 T>C single nucleotide polymorphisms were not associated with ESCC risk. The MBD4 rs3138355 G>A polymorphism was associated with a significantly decreased risk of ESCC among male and older patients. The MBD4 rs3138355 GG genotype was associated with a decreased risk of ESCC among male patients and the elderly. Additional, larger studies are required to confirm these current findings.